24-hour central blood pressure and intermediate cardiovascular phenotypes in untreated subjects - Bednarek, Agnieszka (Am J Cardiovasc Dis, 2014)
Background: Recently, 24-hour monitoring of central systolic blood pressure (SBP) has become available. However, the relation between end-organ damage and the 24-hour central SBP profile and variability has not so far been analyzed. Therefore, the aim of this cross-sectional study was to evaluate the relation between 24-hour central SBP, 24-hour central SBP profile as well as central SBP short-term variability and parameters of cardiac and vascular intermediate phenotypes. Methods: The study group consisted of 50 patients with newly diagnosed, untreated hypertension (age 40.4 ± 11.5 years, 35 men) and 50 normotensive subjects (age 38.3 ± 12.0 years, 35 men). Applanation tonometry of the radial artery and the “n-point forward moving average” method were used to determine 24-hour central SBP. Each study participant underwent echocardiography and carotid ultrasonography. Results: 24-hour, daytime, and nighttime central SBP was related to left ventricle end-diastole diameter (p < 0.05), left ventricular mass index (p < 0.001), relative wall thickness (p < 0.05), E/E’ ratio (p < 0.01), and left atrium volume (p < 0.01). The nocturnal central SBP fall was not related to any of the mentioned parameters, whereas parameters of short-term variability were related to IMT in hypertensives only (p < 0.05). Conclusions: The present study showed that 24-hour central SBP is related to intermediate cardiac phenotypes as assessed by echocardiography whereas short-term central SBP variability is mainly related to vascular phenotype as determined by IMT.